Synthesis and in vitro evaluation of 1,2,4-triazolo[1,5-a][1,3,5]triazine derivatives as thymidine phosphorylase inhibitors - Bera, H.; Dolzhenko, Anton; Sun, L.; Dutta Gupta, S.; Chui, W. (2013)
In our lead finding program, a series of 1,2,4-triazolo[1,5-a][1,3,5]triazine derivatives were synthesized, and their in vitro thymidine phosphorylase inhibitory potential was explored. Among the different derivatives, compounds having keto group (C = O) at C7 and thioketo group (C = S) at C5 positions showed varying degrees of TP inhibitory activity comparable with positive control, 7-deazaxanthine (7-DX, 2) (IC50 value = 42.63 µm). Enzyme inhibition kinetics study suggested that compound IVn behaved as a mixed-type inhibitor of the enzyme with respect to thymidine (dThd) as a variable substrate. Compound IVn was also found to inhibit PMA-induced MMP-9 expression in MDA-MB-231 cells at sublethal concentrations. Computational docking study was performed to illustrate the enzyme inhibition kinetics and to explore the ligand-enzyme interactions. © 2013 John Wiley & Sons A/S.